(untitled) (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2024)
The dissemination of Islamic media is progressively expanding. It is no longer confined to conventional platforms such as television, radio, and print media but has extended to social media platforms. Utilization of social media devices for the purpose of Islamic propagation is also undertaken by community organizations, one of which is Nahdlatul Ulama. However, there remains a lack of comprehensive insight into Nahdlatul Ulama’s media broadcasting landscape. Thus, this article aims to elucidate the Islamic media broadcasting map of Nahdlatul Ulama in East Java. The research adopts a mixed-method approach, where quantitative data is extracted from big data on the internet, while qualitative supporting data is gathered through in-depth interviews. The research findings reveal that the distribution map of media utilized by Nahdlatul Ulama in East Java comprises predominantly Instagram, accounting for 97.3% of 152 data points, followed by YouTube (92.1%), Facebook (92.1%), the organization’s official website (86.8%), and TikTok (31.5%). Content disseminated through these media platforms is predominantly focused on information, promotion, and inspirational content.